Venoarteriovenous ECMO in Concomitant Acute Respiratory Distress Syndrome and Cardiomyopathy Associated with COVID-19 Infection - Zachary R. Bergman; Saranya Prathibha; Brent D. Bauman; Demetris Yannopoulos; Melissa E. Brunsvold (Case Reports in Critical Care)
In the most severe cases, novel coronavirus (SARS-CoV-2) infection leads to Acute Respiratory Distress Syndrome which may be refractory to standard medical interventions including mechanical ventilation. There are growing reports of the use of venovenous (VV) extracorporeal membrane oxygenation (ECMO) in these cases. A subset of critically ill COVID-19 patients develops cardiomyopathy as well, manifested by cardiogenic shock with reduced ejection fraction, dysrhythmias, and subsequent increase in mortality. One strategy for managing ARDS with an element of cardiogenic shock is venoarteriovenous (VAV) ECMO. Less than 1% of the cases in the worldwide ELSO COVID-19 database employed any form of hybrid cannulation. To date, there has only been one reported case of patient salvage with arterial or partial arterial support. We present a case that demonstrates the potential role of VAV ECMO in the case of concomitant severe ARDS with cardiomyopathy in the setting of COVID-19 infection.